LIRIK LAGU DALAM ALBUM SAURA KARYA GRUP BAND MANJAKANI; KAJIAN STILISTIKA - Pratiwi, Anggi Putri Anggi; Seli, Sesilia; Wartiningsih, Agus (Universitas Tanjungpura, 2024)
This Study Aims To Improve The Reader's Understanding Of The Stylistics Of The Song Lyrics In The Album Saura The Work Of The Manjakani Band Group. This Research Is In The Form Of A Qualitative Descriptive Method, The Data Sources Are Muhammad Taufan And Nabila Syafani As The Creators Of Song Lyrics As Well As Members Of The Manjakani Band, With Data Namely Rhyme, Rhythm, Tone, Atmosphere, Concrete Words, Connotative Words, Greeting Words, Natural Reality Object Words, Declarative Sentences, Imperative Sentences, Expositions, And Imagery. The Result Of This Research Is Rhyme On The Song Lyrics In The Album Saura The Work Of The Manjakani Band Includes Assonance And Allitration, But What Dominates Is Assonance. Rhythm Includes Efony And Cacafonic Rhythms, Which Dominates The Efony. The Dominating Tone And Atmosphere Is Longing. The Types Of Words Used By The Author Include Connotative Words, Concrete Words, Greeting Words Or Real Name Realities, And Words With Natural Reality Objects, But What Dominates Are Connotative Words. The Types Of Sentences Used By The Author Include Declarative, Imperative, And Minor Sentences, But Declarative Sentences Dominate. The Figures Of Speech Obtained Include Simile, Metaphor, Personification, Hyperbole, Paradox, And Metonymy, But Personification Figure Dominates. The Imagery Obtained In The Lyrics Of This Song Includes Visual, Auditory, Tasting, Moving, And Intellectual Imagery, But Visual Imagery Dominates.